2011
DOI: 10.1111/j.1600-0463.2011.02803.x
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelial cells can detach from the mesentery and differentiate into macrophage-like cells

Abstract: Peritoneal cell suspension is composed of heterogeneous cell population. Macrophages are the most numerous cells among them. They can originate from different sources and can be resident, exudate and elicited. When we used Freund's adjuvant to elicit peritoneal macrophages, cells having large amount of caveolae on their plasma membrane appeared in the peritoneal wash. The number of these caveolae-rich cells increased by the time of the Freund's adjuvant treatment. Although their morphology was different form f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…Type II receptor then trans-phosphorylates (activates) the signalling receptor (type I) that can initiate Smad2/3 signalling pathway. We have previously demonstrated [12] Freund's adjuvant treatment also induced a significant amount of TGF-β production in mesothelial cells that was secreted into the peritoneal cavity. The level of TGF-β highly correlated with the kinetics of the inflammation, and transforming mesothelial cells also expressed TGFβRII [13].…”
Section: Inflammation Induces Epithelial-mesenchymal Transition (mentioning
confidence: 98%
See 3 more Smart Citations
“…Type II receptor then trans-phosphorylates (activates) the signalling receptor (type I) that can initiate Smad2/3 signalling pathway. We have previously demonstrated [12] Freund's adjuvant treatment also induced a significant amount of TGF-β production in mesothelial cells that was secreted into the peritoneal cavity. The level of TGF-β highly correlated with the kinetics of the inflammation, and transforming mesothelial cells also expressed TGFβRII [13].…”
Section: Inflammation Induces Epithelial-mesenchymal Transition (mentioning
confidence: 98%
“…DURING INFLAMMATION INDUCED EMT During inflammation-induced EMT mesenteric mesothelial cells start to express macrophage markers (OX43, ED1) as well [12,52], suggesting that they might be transformed into macrophage-like cells [53]. Our previous data showed that under inflammatory stimuli the number of peritoneal macrophages dramatically increased [54].…”
Section: Mesothelial Cell-macrophage Transition (Mmt)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, these therapies cannot prevent PMC loss, which plays a critical role in causing PF [9]. Previous studies have suggested that PMCs showed strong labeling with antibodies against Nestin, which is a speci c marker for multifunctional, multilineage progenitor cells, indicating that these cells represent a "young", not entirely differentiated cell population [10]. The intermediate lament protein…”
Section: Introductionmentioning
confidence: 99%